2-Methyl-6-(phenylethynyl) pyridine (MPEP) reverses maze learning and PSD-95 deficits in Fmr1 knock-out mice - Gandhi, Réno M.; Kogan, Cary S.; Messier, Claude (Frontiers in Cellular Neuroscience, 2014)
Fragile X syndrome (FXS) is caused by the lack of expression of the fragile X mental retardation protein (FMRP), which results in intellectual disability and other debilitating symptoms including impairment of visual-spatial functioning. FXS is the only single-gene disorder that is highly co-morbid with autism spectrum disorder and can therefore provide insight into its pathophysiology. Lack of FMRP results in altered group I metabotropic glutamate receptor (mGluR) signalling, which is a target for putative treatments. The Hebb-Williams (H-W) mazes are a set of increasingly complex spatial navigation problems that depend on intact hippocampal and thus mGluR-5 functioning. In the present investigation, we examined whether an antagonist of mGluR-5 would reverse previously described behavioural deficits in Fmr1 KO mice. Mice were trained on a subset of the H-W mazes and then treated with either 20 mg/kg of an mGluR-5 antagonist, 2-Methyl-6-(phenylethynyl) pyridine (MPEP; n = 11) or an equivalent dose of saline (n = 11) prior to running test mazes. Latency and errors were dependent variables recorded during the test phase. Immediately after completing each test, marble-burying behavior was assessed which confirmed that the drug treatment was pharmacologically active during maze learning. Although latency was not statistically different between the groups, MPEP treated Fmr1 KO mice made significantly fewer errors on mazes deemed more difficult suggesting a reversal of the behavioural deficit. MPEP treated mice were also less perseverative and impulsive when navigating mazes. Furthermore, MPEP treatment reversed PSD-95 protein deficits in Fmr1 KO treated mice, whereas levels of a control protein (β-tubulin) remained unchanged. These data further validate MPEP as a potentially beneficial treatment for FXS. Our findings also suggest that adapted H-W mazes may be a useful tool to document alterations in behavioural functioning following pharmacological intervention in FXS.